Enhancing Kiwi Leaf Disease Detection Through Advanced Convolutional Neural Networks and Transfer Learning Techniques - Li, Muzi (Journal of Computer Science and Software Applications, 2024)
To enhance the effectiveness of the kiwi leaf disease recognition model, a novel approach utilizing a convolutional neural network (CNN) has been developed. Initially, a comprehensive dataset comprising 7,310 images of kiwi leaves afflicted with four types of diseases—brown spot, ulcer, mosaic, and anthracnose—was compiled. Following the dataset creation, pre-processing steps were applied to optimize the data for model training. Subsequently, a nine-layer CNN model, inspired by AlexNet, was constructed. Additionally, transfer learning techniques were employed, leveraging pretrained models such as VGG16, VGG19, InceptionV3, and InceptionV4, which were initially trained on the ImageNet dataset, for the task of kiwi leaf disease classification and recognition. Experimental outcomes indicate that models trained with transfer learning exhibit superior classification performance and faster convergence rates. Data augmentation was also found to enhance data diversity and mitigate overfitting. Notably, utilizing the VGG19 pre-trained model, the combined application of transfer learning and data augmentation achieved a classification accuracy of 96.73%.